Z bioelektrično impedančno analizo izmerjene vrednosti faznega kota in mase telesnih celic pri otrocih s cerebralno paralizo glede na stopnjo funkcijskih zmožnosti grobega gibanja - Lenardič, Jasna (Rehabilitacija (Ljubljana), 2024)
In order to effectively identify any deviations in the child’s nutritional status and follow-up possible changes, it is important to use as reliable and accurate assessment methods as possible. We wanted to check the reliability of individual variables obtained by bioelectrical impedance analysis (BIA) in children with cerebral palsy (CP), especially phase angle (PA) and body cell mass (BCM) values and compared them with the values of their healthy peers. At the same time, we wanted to determine whether there is a correlation between the level of Gross Motor Function Classification System (GMFCS) levels and BCM and PA values. Methods: We searched the PubMED database using the keywords "bioelectrical analysis" OR "BIA" OR "bioelectrical" OR "body composition") AND "Cerebral Palsy" for all articles that were published until January 25, 2024. Results: Using the selected keywords, we found 206 articles, and then, taking into account the inclusion criteria, we included four articles in the literature review, in which the authors studied PA and BCM values in children with CP (328 children) according to the GMFCS level or in comparison with their healthy peers (220 children). We found that the values of BCM and PA are lower in children with CP compared to their healthy peers, and the values of both variables are lower in children with a higher level of GMFCS. Conclusion: Due to the heterogeneity of measurement methods and protocols, reported BCM and PA values in the available literature are diverse. For greater reliability of both variables, it would be necessary to standardise the measurement protocol and include a larger population of children with CP in the future.
Keywords: bioelectrical impedance analysis; bioelektrična impedančna analiza; body cell mass; Cerebral Palsy; cerebralna paraliza; Child; fazni kot; masa telesnih celic; otrok; phase angle; rehabilitacija; rehabilitation